Mercury distribution around the Spolana chlor-alkali plant (central Bohemia, Czech Republic) after a catastrophic flood, as revealed by bioindicators - Suchara, Ivan; Sucharová, Julie (Environmental pollution (Barking, Essex, 2008)
The current mercury concentrations in moss Hypnum cupressiforme, in forest floor humus and in oak and pine bark were determined in a 10-km radius around a chlor-alkali plant affected by a flood in 2002. Similar distribution patterns of Hg had accumulated in four bio-indicators, irrespective of different Hg concentrations in the analysed biological matrices. No accumulation of extremely Hg-contaminated materials was found in the flooded parts. The bio-indicators, used alone or in combination, can be recommended for effective and reliable determination of Hg contamination levels around Hg sources.
Keywords: Environmental Pollutants; monitorování životního prostředí; látky znečišťující životní prostředí; dub (rod); látky znečišťující půdu; Quercus; Disasters; Česká republika; kůra rostlin; Environmental Monitoring; katastrofy; rtuť; Czech Republic; Chemical Industry; chemické látky znečišťující vodu; Pinus; chemický průmysl; Soil Pollutants; Mercury; Water Pollutants, Chemical; Soil; Bryopsida; mechy; Plant Bark; borovice; půda